CMCS: a cross-layer mobility-aware mac protocol for cognitive radio sensor networks - Zareei, Mahdi (Springer, 2016)
Cognitive radio sensor networks (CRSNs) are multi-channel-capable networks that inherit some of the challenges of traditional wireless sensor networks (WSNs), such as limited power source and hardware capacity. In several CRSN applications, such as surveillance and intelligent transportation systems, node mobility is a typical assumption. However, as a node changes its physical location, spectrum mobility may also follow. Therefore, the treating of node mobility in CRSN imposes new challenges on all network layers, especially in the data link layer. In this paper, we propose a novel cross-layer mobility-aware medium access control (MAC) protocol for CRSN. We also propose an efficient spectrum-aware cluster formation and maintenance. The proposed scheme is more robust against primary users' activity as well as node mobility in a CRSN because it integrates spectrum sensing at the physical (PHY) layer with packet scheduling at the MAC layer. Simulation results show that the proposed protocol guarantees about 60 % more common channels per cluster in a higher node ratio. Moreover, the proposed MAC protocol outperforms existing protocols (e.g., CogMesh, cluster-based MAC, and KoN-MAC) in terms of the packet delivery ratio, energy consumption, and delay, by up to 5, 30, and 25 %, respectively.